2014
DOI: 10.5505/tjtes.2014.36589
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic wound dehiscence after penetrating keratoplasty

Abstract: BACKGROUND:We aimed to evaluate the risk factors, clinical features and outcomes of surgery for traumatic wound dehiscence (TWD) following penetrating keratoplasty (PK).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
10
1
4
Order By: Relevance
“…18,19 About a third of the patients in our study had their wound dehiscence occur within 1 year of PK, indicating that the risk for wound dehiscence is highest in the first postoperative year; others have reported similar conclusions. 20 These results suggest that the use of eye protection during the first postoperative year would reduce the likelihood of wound dehiscence in patients who received a graft. On the other hand, our study also revealed that the time to dehiscence post-PK varied widely, from 51 days to 31 years, with the average time being about 10 years posttransplant, which is longer than the previously reported 7.5 years.…”
Section: Discussionmentioning
confidence: 92%
“…18,19 About a third of the patients in our study had their wound dehiscence occur within 1 year of PK, indicating that the risk for wound dehiscence is highest in the first postoperative year; others have reported similar conclusions. 20 These results suggest that the use of eye protection during the first postoperative year would reduce the likelihood of wound dehiscence in patients who received a graft. On the other hand, our study also revealed that the time to dehiscence post-PK varied widely, from 51 days to 31 years, with the average time being about 10 years posttransplant, which is longer than the previously reported 7.5 years.…”
Section: Discussionmentioning
confidence: 92%
“…There is a risk of corneal WD in the postoperative cornea. The incidence of WD after corneal transplantation ranges from 0.6% to 5.8% [ 3 , 5 , 6 ], and one major reason is trauma reported to be 1.28%–2.53% [ 5 8 ]. In our study, the incidence of WD after keratoplasty was 1.0%, lower than the other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Oküler yapılar, vücuttaki diğer yapılarla karşılaştırıldığında çok küçük bir alan kaplamalarına rağmen el ve ayaklardan sonra travmaya en çok maruz kalan üçüncü organımızdır. 3 PKP sonrası travmatik yara ayrılması insidansı %0,6-5,8 olarak bildirilmiştir. 4 PKP sonrası gelişen travmatik rüptürlerde prognozun daha kötü olduğu bilinmektedir.…”
Section: Discussionunclassified